O poder da embalagem na decisão de compra do consumidor de detergente em pó: uma análise com consumidores de Araguaína/TO. - Veloso, Catiane Nascimento (Universidade Federal do Tocantins, 2020)
The present work presents the importance that the packaging has to influence a consumer in the choice of a product. It aims to analyze the power of packaging on consumers. Specifically, it seeks to show the consumption of detergent powder by checking which criteria influence the choice of purchase of a consumer, as well as the behavior of the same in relation to the packaging. The methodology used in this study was a descriptive field research with a quantitative approach, using a questionnaire composed of 10 closed questions. The research was carried out with consumers from the city of Araguaína-TO. From this research it was possible to realize that the packaging has a valuable role in the time to take the consumer to opt for a product, because through the collected data there is a large percentage of consumers who see the packaging as something important not only to pack the Product properly, but also communicate directly with the customer, making it a silent seller.